Cytoprotective and Cytotoxic Effects of Rice Bran Extracts on H2O2- Induced Oxidative Damage in Human Intestinal Caco-2 Cells - Jittorntrum, Bunyada; Chunhabundit, Rodjana; Kongkachuichai, Ratchanee; Srisala, Supanart; Visetpanit, Yupin (Thai Journal of Toxicology, 2020)
Oxidative stress is considered to play a prominent role in the causation of chronic diseases. At present, Rice Science Center, Thailand used plant biotechnology technique to develop new rice strains with increasing nutritive values. Some rice varieties such as Sinlek brown rice and Riceberry pigmented rice showed high levels of antioxidant contents and activities, especially in bran portion. Therefore, the aim of this study was to determine the effects of these bran extracts on H2O2-induced oxidative stress in Caco-2 cells. Human intestinal Caco-2 cells were co-incubated with the bran extracts and H2O2 for 3 h. Cytotoxic effects of both bran extracts were also evaluated and cell viability measured by MTT assay. Cell growth was inhibited in dose- and time-dependent manner by both bran extracts. The doses at which non-toxic and approximate to IC50 were used to determined effects of the rice bran extracts on H2O2 induced oxidative stress. Non-toxic concentrations of both bran extracts protected cells against H2O2- induced oxidative stress as antioxidant property. On the other hand, high concentrations enhanced oxidative stress mediated reduction of cell viability. This may result from the pro-oxidant activity that express at high concentrations of the extracts. Sinlek bran extract exhibited antioxidant and pro-oxidant activity higher than Riceberry bran. In addition, the high concentrations of both bran extracts inhibited cell growth in dose and time-dependent manner. Further studies are needed to clarify the potential activities and properties of these bran extract before using as supplement in food or medicine.